Respiratory Symptoms, Immunological Changes, Ventilatory Capacity, and Bronchial Responsiveness in Welders - Saso Stoleski; Jovanka Karadzinska-Bislimovska; Dragan Mijakoski (ID Design 2012/DOOEL Skopje, 2012)
Objective: To evaluate the effect of workplace exposure and its duration on respiratory symptoms, atopic status, ventilatory capacity, and bronchial responsiveness in welders. Material and Methods: We performed a cross-sectional study including 39 males working as stainless steel welders and an equal number of male office workers matched by age, duration of employment and smoking status. Respiratory symptoms and detailed smoking history were recorded by questionnaire. Evaluation of examined subjects included skin prick tests to common inhalant allergens, spirometry, and histamine challenge. Results: We found non-significantly higher prevalence of respiratory symptoms in the last 12 months in welders with significant difference for cough (P = 0.043) and phlegm (P = 0.009). Prevalence of sensitization to common inhalant allergens was similar in both welders and controls. Mean values of spirometric parameters was lower in welders with significant difference for MEF50 (P = 0.008) and MEF75 (P = 0.000). Prevalence of bronchial hyperresponsiveness (BHR) was higher in welders with significant difference for borderline BHR (P = 0.038). Adverse respiratory effects were more expressed in welders with duration of workplace exposure more than 12 years compared to those exposed less than 12 years. Conclusion: Our data suggest that workplace exposure in welders may lead to respiratory impairment which is close related to its duration.
Keywords: bronchial hyperresponsiveness; Questionnaire; Spirometry; skin prick test; welding